Автоматизований модуль керування складським роботом-контролером - Шевченко, А. А.; Хрустальова, С. В. (ХНУРЕ, 2025)
This article presents an analysis and idea for improving the automated control module of a warehouse robot-controller to meet the needs of medium sized Internet businesses selling household goods online. An overview of existing warehouse automation systems from various companies is presented, their advantages and disadvantages are identified, and conclusions are drawn. An idea for improving the identified disadvantages and methods for its implementation are considered, which could increase the efficiency of the warehouse and improve the business.
Keywords: робот-контролер; керування складським роботом